Molecular and Functional Characterization of CaNAC035, an NAC Transcription Factor From Pepper (Capsicum annuum L.) - Zhang, Huafeng; Ma, Fang; Wang, Xinke; Liu, Suya; Saeed, Ul Haq; Hou, Xiaoming; Zhang, Yumeng; Luo, Dan; Meng, Yuancheng; Zhang, Wei; Abid, Khan; Chen, Rugang (Frontiers in Plant Science, 2020)
NAC (NAM, ATAF1/2, and CUC2) proteins are the plant-specific transcription factors (TFs) which are important in plant response to abiotic stresses. However, knowledge about the functional role that NACs play in pepper abiotic stress tolerance is limited. In this study, we isolated a NAC TF gene, CaNAC035, from pepper (Capsicum annuum L.), where the protein is localized in the nucleus and functions as a transcriptional activator. CaNAC035 expression is induced by low and high temperatures, osmotic stress, salt, gibberellic acid (GA), methyl-jasmonic acid (MeJA), salicylic acid (SA), and abscisic acid (ABA). To understand the function of CaNAC035 in the abiotic stress responsep, we used virus-induced gene silencing in pepper to knockdown the CaNAC035 and overexpressed the CaNAC035 in Arabidopsis. The results showed that pepper seedlings in which CaNAC035 was silenced, showed more damage than the control pepper plants after cold, NaCl, and mannitol treatments. Correspondingly increased electrolyte leakage, a higher level of malondialdehyde (MDA), H2O2, and superoxide radicals were found after cold treatments. CaNAC035-silenced seedlings exhibited lower chlorophyll content while CaNAC035-overexpressed Arabidopsis plants had higher germination rate and fresh weight after mannitol and NaCl treatments. We also reported 18 proteins that potentially interact with CaNAC035 and may participate in processes such as the stress response, resistance, and photosynthesis. Our results suggest that CaNAC035 is a positive regulator of abiotic stress tolerance in pepper which acts through multiple signaling pathways.